Temperature and relative humidity monitoring in the traditional Chinese painting gallery of the Shanghai Museum East - Shen Jingyi (E3S Web of Conferences)
The Shanghai Museum East has been open to the public in 2024. As the stability of temperature and relative humidity is directly relevant to the safety of collections, it is important to find out the real case in the first year. Since the museum has been equipped with an environment monitoring system, it is possible to understand temperature and relative humidity distribution in galleries and showcases. The traditional Chinese painting gallery was among the last group of galleries open to the public, as the traditional paper is more sensitive to improper temperature and relative humidity than other collections, prolonging the time period for preparing the conservative measures in the gallery. Even after the gallery was open to the public, it was still important to monitor temperature and relative humidity in the gallery, especially in the showcases. Since most showcases were larger than 5 m3, the control of relative humidity was a challenge to the conservation staffs. By analysing the measured data with statistical methods, it was determined that most showcases maintained proper temperature and relative humidity in most of the time. However, individual showcases showed abnormal relative humidity data, which may be relevant to the position of sensors, the location of showcases, the tightness of showcases, and the working condition of RH controlling machines. The corresponding treating strategies are also provided.